Предмет: Алгебра, автор: Аноним

корень из (((3b+a^(2))/(2a))+ корень из 3b) + корень из (((3b+a^(2))/(2a))- корень из 3b)

Ответы

Автор ответа: ARHO
0
 sqrt{ frac{3b+a^{2}}{2a}+ sqrt{3b}  } + sqrt{ frac{3b+a^{2}}{2a}- sqrt{3b}  } =
=sqrt{ frac{(sqrt{3b})^2+a^{2}}{2a}+  frac{2asqrt{3b}}{2a}   } + sqrt{ frac{(sqrt{3b})^2+a^{2}}{2a}-  frac{2asqrt{3b}}{2a}   } =
=sqrt{ frac{(a+sqrt{3b})^{2}}{2a} } + sqrt{ frac{(a-sqrt{3b})^{2}}{2a} } = frac{a+sqrt{3b}}{sqrt{2a}} + frac{a-sqrt{3b}}{sqrt{2a}}= frac{2a}{sqrt{2a}}=sqrt{2a}
Похожие вопросы